1
$\begingroup$

I was looking at the following proof and I'm having trouble understanding how the first part of the second line works?

Specifically: how were they able to pull the z out of the right summation?

enter image description here

$\endgroup$
3
$\begingroup$

Going from the first line to the beginning of the second line, you aren't pulling $z$ out of the right summation. You are simply substituting $$ P(h(X,Y) = z) = \sum_{\{(x,y): h(x,y) = z\}}P(X=x,Y=y). $$ This is true by definition of a probability mass function. You add over the input pairs $(x,y)$ such that $h(x,y) = z$.

On the other hand, going from the beginning of the second line to the right side of the second line, that isn't always true. It's true most of the time, however. I wouldn't worry about this re-arranging the order of summations, if I were you.

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

You are able to remove z out of the summation because you are explicitly looking for the probability when function value = z.

For example, consider a univariate random variable which is

z = x + y w.p. 0.2,

z = x-y w.p. 0.3 and

z = 2x w.p. 0.5. where x = 1, y = 0.

Then, E[Z] = 1 * 0.3 + 1 * 0.2 + 2 * 0.5 = 1 * 0.5 + 2 * 0.5.

= 1 * P(z=1) + 2 * P(z=2)

This is essentially what you are doing when you are getting z out of the summation.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.